Impact of EU cross-border cooperation programmes on regional development : the case of Edirne and Kırklareli - Bozkurt, Serkan (My University, 2019)
Sınır etkisinin azaltılmasına katkı sağlayan sınır ötesi işbirliği (SÖİ) programları AB Bölgesel Politikası kapsamında oluşturulan önemli politika araçlarındandır. 1990'da Interreg girişimi olarak başlayan ve AB üyesi ülkelerin bölgeleri için yürütülen SÖİ programlarının yanı sıra, AB'nin dış sınırlarında yer alan bölgelerin kalkınması için de Katılım Öncesi Yardım Aracı (IPA) ve Avrupa Komşuluk Aracı (ENI) altında bir takım işbirliği araçları vardır. Türkiye, adaylık durumu ve coğrafi durumu nedeniyle IPA ve ENI altında yürütülen AB SÖİ programlarına katılmaktadır. Bu çalışmanın örnek vaka incelemesi olan Edirne-Kırklareli sınır bölgesi, 2003'ten beri Türkiye'de uygulanan bütün SÖİ programlarına dahil olmuştur. Bu tezde, AB SÖİ programlarının sınır bölgelerinin kalkınmasındaki etkisi ve katkıları Edirne-Kırklareli sınır bölgesinin örnek vaka çalışması olarak incelenmesi suretiyle ussal kurumsalcılık yaklaşımına göre analiz edilmektedir. Bu çalışmadaki bulgular ışığında, AB SÖİ programlarının AB'deki sınır alanlarının bölgesel kalkınmasına önemli bir katkı sağladığı, ancak bu programların Edirne-Kırklareli sınır bölgesinde bölgesel kalkınmaya etkisi ve katkısının kültür, turizm ve çevre alanlarıyla sınırlı olduğu savunulmaktadır.

Cross-border cooperation programmes (CBC) are among the important policy instruments created under the EU Regional Policy to contribute to reducing the adverse effects of borders. In addition to CBC programmes for European regions, which began as Interreg initiatives in 1990, there are also cooperation instruments to support regional development of border regions along the EU's external borders under the Instrument for Pre-accession Assistance (IPA) and European Neighbourhood Instrument (ENI). Turkey participates in CBC programmes funded by the EU under IPA and ENI mechanisms due to the candidacy status of Turkey and its geographical location. Edirne-Kırklareli border region, which is examined as a case in the thesis, is covered by all CBC programmes implemented in Turkey since 2003. In this study, the contributions and impact of the EU CBC programmes on regional development of border areas are analysed through scrutinizing the border region involving Edirne and Kırklareli as a case study from a rationalist institutionalism perspective. Considering the analyses of this study, it is argued that EU CBC programmes have significant contribution to regional development of border areas in the EU whereas contribution and impact of these programmes on regional development of Edirne-Kırklareli border region is limited to the fields of culture, tourism and environment.
Keywords: AB Sınır Ötesi İşbirliği Programları; Avrupa Birliği; Avrupa Bölgesel İşbirliği; Border Regions; Bölgesel Kalkınma; Bölgesel Politika; EU Cross-border Cooperation Programmes; European Territorial Cooperation; European Union; International relations; Regional Policy; Sınır Bölgeleri Regional Development; Uluslararası ilişkiler